Increased number of deaths during a chikungunya epidemic in Pernambuco, Brazil - Carlos Alexandre Antunes de Brito; Maria Glória Teixeira (Memorias do Instituto Oswaldo Cruz)
In early 2016, it was suspected that there were more deaths in Pernambuco than in previous years during an epidemic of chikungunya. This study tested whether there was an increased number of deaths and, if so, whether this increase could be related to a chikungunya epidemic. Indeed, there was an increase of 4235 deaths in 2016 compared to the average of the four previous years, and the highest differences were found during the peak period of the epidemic. It was evident that not all of these deaths could be attributed to complications of chikungunya. However, considering the temporal overlap, some of these deaths may have been caused by the aggravation of pre-existing comorbidities or complications caused directly by chikungunya virus infection.